CHLAMYDOMONAS REINHARDTII SEC23 PARALOGS AND THEIR PHYLOGENETIC RELATIONSHIPS - M. Aksoy; A. R. Grossman; Ö. Musul (Journal of Animal and Plant Sciences, 2022)
C. reinhardtii has two putative SEC23 genes, CrSEC23A and CrSEC23B. The encoded polypeptides are only ~18.9% identical, suggesting that they might have different functions. It is not clear whether SEC23 paralogs have same or different functions in diverse organisms. Interestingly, our alignment and homology modeling showed that CrSEC23B does not have the conserved SEC24 binding motif (VFR), but instead appears to have an LPA motif in the same position. While LPA might be part of a novel SEC24 binding motif, CrSEC23B might have an alternate function that is either associated with or independent of COPII. Our results also show SEC23 orthologs in various organisms have variations in the putative SEC24 binding motif. Phylogenetic analyses place the SEC23 orthologs into two clusters that we designated group A (conventional; CrSEC23A-like orthologs) and group B (unconventional; CrSEC23B-like orthologs). Our results suggest that many photosynthetic organisms have a divergent SEC23 paralog. This divergence is not seen in animals. We hypothesize that divergent (unconventional) SEC23 paralogs might be the result of gene duplication and divergence that may facilitate specific aspects of trafficking. Since we only identified the B-like proteins in photosynthetic lineages, we hypothesize that B-like proteins may not have been present in the common ancestor involved in the primary endosymbiotic event.
Keywords: Chlamydomonas reinhardtii; SEC23 paralogs; gene duplication; secretory pathway; COPII